Complete Genome Sequence of Croceibacter atlanticus HTCC2559(T) - Oh, Hyun-Myung (American Society for Microbiology, 2010)

(untitled)
Here we announce the complete genome sequence of Croceibacter atlanticus HTCC2559(T), which was isolated by high-throughput dilution-to-extinction culturing from the Bermuda Atlantic Time Series station in the Western Sargasso Sea. Strain HTCC2559(T) contained genes for carotenoid biosynthesis, flavonoid biosynthesis, and several macromolecule-degrading enzymes. The genome confirmed physiological observations of cultivated Croceibacter atlanticus strain HTCC2559(T), which identified it as an obligate chemoheterotroph.